The prevalence of predialysis hyperkalemia and associated characteristics among hemodialysis patients: The RE‐UTILIZE study. Issue 3 (17th January 2022) - Agiro, Abiy; Duling, Ian; Eudicone, James; Davis, Jill; Brahmbhatt, Yasmin G.; Cooper, Kerry
Abstract: Introduction: Hyperkalemia (HK), defined as serum potassium (K + ) >5.0 mEq/L, is an independent predictor of mortality in patients on maintenance hemodialysis (HD). This study investigated the annual prevalence of HK and examined patient characteristics potentially associated with a higher annual HK prevalence. Methods: This retrospective observational cohort study used Dialysis Outcomes and Practice Patterns Study (DOPPS) survey data from US patients undergoing in‐center HD thrice weekly from 2018 to 2019. The primary endpoint was the proportion of patients with any predialysis HK (K +  >5.0 mEq/L) within 1 year from the index date (date of DOPPS enrollment), using the first hyperkalemic K + value. Secondary endpoints were the proportion of patients with moderate‐to‐severe (K +  >5.5 mEq/L) or severe (K +  >6.0 mEq/L) HK. Findings: Overall, 9347 patients on HD were included in this analysis (58% male and 49% aged >66 years). Any predialysis HK (K +  >5.0 mEq/L) occurred in 74% of patients within 1 year of the index date, 52% within 3 months, and 38% within 1 month. The annual prevalence of moderate‐to‐severe and severe HK was 43% and 17%, respectively. Recurrent HK (at least two K +  >5.0 mEq/L within 1 year) occurred in 60% of patients, and 2.8% of patients were prescribed an oral K + binder. Multivariable logistic regression analysis showed younger age, female sex, Hispanic ethnicity, and renin–angiotensin–aldosterone system inhibitor use were significantly associated with a higher annual prevalence of any predialysis HK, while Black race, obesity, recent initiation of HD, and dialysate K + bath concentration ≥3 mEq/L were associated with a lower prevalence of HK. Discussion: The annual prevalence of predialysis HK and recurrence were high among US patients on HD, whereas oral K + binder use was low. Further studies are needed to understand the impact of dialysate K + bath concentrations on predialysis HK among patients on HD.